The psychographic segmentation of the unit trust investors by factor analysis for Malaysia financial services - Rohaizat Baharun, author; Abu Bakar Abdul Hamid, author; Ahmad Sharifuddin Shamsuddin, author; Nor Zafir Md. Salleh, author; Norzaidahwati Zaidin, 1967-, author; Zuraidah Sulaiman, author; Mediterranean Conference for Academic Disciplines (2009 : Malta) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL